Estimasi Karbon Tersimpan pada Tegakan Pohon di Hutan Pantai Pulau Kotok Besar, Bagian Barat, Kepulauan Seribu - Mohamad Fazri Hikmatyar; Tubagus Muhammad Ishak; Ario Putro Pamungkas; Sayyidah Sofie Annisa Mujahidah; Alfan Farhan Rijaludin (Al-Kauniyah: Jurnal Biologi, 2015)
The high activity of urban communities anthropogenic especially in Jakarta City cause high rates of carbon emissions. This problem is increased with the high rate of deforestation which is high enough in urban areas. One of ecosystem that can reduce carbon emissions is coastal forest ecosystem. Forests can reduce carbon emissions in the atmosphere and storing it in various compartments such as vegetation, litter and soil organic matter. One of the islands which have a coastal forest with good enough condition is Kotok Besar Island, the cluster of Seribu Islands. This study aims to estimate the carbon stored in tree stands at coastal forest region of west side of Kotok Besar Island, Seribu Islands. Methods of calculating carbon stock was done by making the observation plots and distributed by random sampling method to calculate diameter at breast height (dbh) and identify the type of tree stands were found in the observation plots. dbh data was inserted into allometric equation to obtain the potential of stored carbon estimates. The results showed that the coastal forest of west side of the Kotok Besar Island have the number of plant species that dominate as many as four species, which consists of Thespesia populnea, Casuarina sp., Calophyllum sp., and Cocos nucifera. Biomass value is 853.94 tons / ha and potential of carbon stored is 426.97 tons/ha.